2015
DOI: 10.1007/s13277-015-3114-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of HPV with genetic and epigenetic alterations in colorectal adenocarcinoma from Indian population

Abstract: Several studies from developing countries have shown human papillomavirus to be associated with colorectal cancers, but the molecular characteristics of such cancers are poorly known. We studied the various genetic variations like microsatellite instability (MSI), oncogenic mutations and epigenetic deregulations like CpG island methylation in HPV associated and nonassociated colorectal cancer patients from Indian population. HPV DNA was detected by PCR using My09/My11 and Gp5+/Gp6+ consensus primers and typed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The HPV positivity ratio reported in these studies was varied between 0% [ 11 , 12 , 17 , 23 , 26 , 32 , 41 , 43 , 45 , 46 , 50 , 59 ] and 100% [ 13 , 54 ]. In most of the case–control studies [ 12 , 17 27 , 29 32 , 35 – 57 ], the positivity ratio for HPV detection was higher in the cancerous samples as compared to the controls, whereas, in some studies [ 28 , 33 , 34 , 58 ], HPV positivity ratio was higher in the controls as compared to the CRC samples. Possible reasons for such population-specific inequalities in HPV detection could be non-modifiable factors such as genetic makeup and socially controllable factors such as health-seeking behaviour and differential access to the health facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPV positivity ratio reported in these studies was varied between 0% [ 11 , 12 , 17 , 23 , 26 , 32 , 41 , 43 , 45 , 46 , 50 , 59 ] and 100% [ 13 , 54 ]. In most of the case–control studies [ 12 , 17 27 , 29 32 , 35 – 57 ], the positivity ratio for HPV detection was higher in the cancerous samples as compared to the controls, whereas, in some studies [ 28 , 33 , 34 , 58 ], HPV positivity ratio was higher in the controls as compared to the CRC samples. Possible reasons for such population-specific inequalities in HPV detection could be non-modifiable factors such as genetic makeup and socially controllable factors such as health-seeking behaviour and differential access to the health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In India, a single case–control study [ 27 ] has been reported so far to find out the association between HPV and CRC. They analysed 93 CRC samples and 30 adjacent/benign controls using L1 gene-specific primers through the PCR technique and identified 6% HPV detection positivity ratio in normal and 36.5% positivity ratio in the CRC samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA1 methylation is observed in approximately 11–14% of breast cancers and 5%–31% of ovarian cancers [93]. BRCA1 methylation is also found in gastric (1.4%) [89], colorectal (10.75%) [94], non-small cell lung (18.6%) [95], bladder (12.1%) [96] and pancreatic cancers (46%) [97]. BRCA2 methylation is reported in NSCLC (42%) [80].…”
Section: Epigenetic Changes Of Dna Damage Repair Genes In Human Cancersmentioning
confidence: 99%
“…[1][2][3] There is evidence for the presence of more than 100 types of HPV in the medical literature. In addition, 15 types of HPV (16,18,35,31,39,51,45,56,52,66,59, 69, 68, 82, and 73) are considered to be highly involved in the pathogenesis of genital cancer in women while HPVs responsible for the warts of genitals and skin (HPV 6,11,43,42,40,44,61,54,72,70, and 81) have lower pathogenicity. [4][5][6] Further, HPV is related to other malignancies including anal, oropharyngeal, penile, vulvar, and HPV-related tumors, which together represent 0.7% of carcinomas in both genera.…”
Section: Introductionmentioning
confidence: 99%